Relationship between hedonic and eudaimonic well-being in pediatric cancer patients - Pérez Mendoza, Aura; Vinaccia Alpi, Stefano; Bethencourt, Rosangela Raleigh (Informes Psicológicos, 2020)
The purpose of this study was to determine the relationship between hedonic and eudaimonic well-being in childhood and juvenile cancer patients in Córdoba, Colombia. The research was cross-sectional, descriptive-correlational. Diener’s Satisfaction with Life questionnaires were applied to measure Ryff’s hedonic well-being and psychological well-being for eudaimonic well-being to a sample of 30 patients diagnosed with cancer in the city of Montería. The results showed optimal levels of eudaimonic and hedonic well-being in the patients. In general, the two variables presented low correlations with the exception of the Self-acceptance dimension of the Ryff scale, which presented a moderate and positive correlation with Satisfaction with life. In conclusion, it is necessary to conduct further research on other variables that can moderate this relationship.